The endosperm microstructure, physical, thermal properties and specific milling energy of spelt (Triticum aestivum ssp. spelta) grain and flour - Warechowska, Małgorzata; Anders, Andrzej; Warechowski, Józef; Bramowicz, Mirosław; Markowska-Mendik, Agnieszka; Rejmer, Wojciech; Tyburski, Józef; Kulesza, Sławomir (Scientific reports, 2023)
Previous research has shown that the endosperm microstructure and physical properties of grain have significance in grain processing and in the development of processing machines. The aim of our study was to analyze the endosperm microstructure, physical, thermal properties, and specific milling energy of organic spelt ( Triticum aestivum ssp . spelta ) grain and flour. Image analysis combined with fractal analysis was used to describe the microstructural differences of the endosperm of spelt grain. The endosperm morphology of spelt kernels was monofractal, isotropic, and complex. A higher proportion of Type-A starch granules resulted in an increased proportion of voids and interphase boundaries in the endosperm. Changes in the fractal dimension were correlated with kernel hardness, specific milling energy, the particle size distribution of flour, and the starch damage rate. Spelt cultivars varied in size and shape of the kernels. Kernel hardness was a property that differentiated specific milling energy, particle size distribution of flour, and starch damage rate. Fractal analysis may be considered as a useful tool for evaluating milling processes in the future.